Penguatan Ideologi Pancasila Melalui Kegiatan Organisasi Kemahasiswaan - Juliana, Sisca; Taqiuddin, Habibul Umam (Fakultas Hukum Universitas Nahdlatul Ulama Nusa Tenggara Barat, 2023)
This research aims to analyze the relationship between student organizations and the strengthening of the Pancasila ideology. Second, to analyze the role of student organizations in strengthening the Pancasila ideology. The research method used by researchers is the library research method. Researchers use library research methods to come up with the latest ideas in the research carried out by researchers. By conducting library research, researchers can utilize all information and thoughts that are relevant to this research. The data collection technique used by researchers utilizes secondary data, namely by collecting materials related to this research originating from books and scientific journals. Next, the data that has been obtained is analyzed qualitatively. The results of this research show, among other things: first, through student organizations the strengthening of the Pancasila ideology can be carried out because basically student organizations are a forum for building student character. Second, in the context of strengthening the Pancasila ideology, student organizations act as guardians of values.